Wunderlich syndrome in pregnancy: life threatening bleeding renal angiomyolipoma in first and third trimesters: two case reports and literature review - Khor, Vincent; Mohd Naim, Mohd Yakob; Fahmy, Omar; Lee, Christopher Kheng Siang (Springer Science and Business Media Deutschland, 2024)
Background: Renal angiomyolipoma (AML) is a prevalent benign tumour of the kidney. However, Wunderlich syndrome, marked by retroperitoneal haemorrhage, remains a rare and critical complication of large AMLs. During pregnancy, AMLs demonstrate an accelerated growth pattern and pose an elevated risk of rupture, leading to massive retroperitoneal haemorrhage. This report presents two compelling cases of life-threatening bleeding AML during the first and third trimesters, shedding light on the urgent need for heightened awareness and management strategies in pregnant women with AML. These cases underscore the novel and crucial aspect of the increased vulnerability of AMLs in pregnancy, emphasizing the importance of timely diagnosis and intervention. Cases presentation: The first patient is a 37-year-old lady who presented at 27 weeks of gestation with foetal distress, abdominal pain and hypovolemic shock. Emergency Caesarean section was performed for possible abruptio placenta, and a large non-expanding retroperitoneal hematoma was found intra-operatively. Post-delivery computed tomography (CT) angiography assessment showed left perinephric hematoma from bleeding AML at the lower pole. She was hemodynamically unstable after CT and underwent an emergency nephrectomy. Post-operative recovery was uneventful. The second patient is a 30-year-old lady who presented with right abdominal pain at 11 weeks of gestation with hypotension and an actively bleeding ruptured AML found on the abdominal MRI. She underwent angioembolization at 12 weeks of pregnancy with a radiation shield to protect the foetus. She recovered well after the procedure and continued her pregnancy. Her baby was born healthy at term with no evidence of any congenital malformation. Conclusions: When dealing with renal angiomyolipoma during pregnancy, multidisciplinary team management is crucial for the best management care. Stable cases can be treated conservatively, while unstable cases may require angioembolization or nephrectomy. The management plan should prioritize the best outcomes for both the mother and foetus. During the first trimester, angioembolization is safe and effective in controlling bleeding. However, minimizing radiation exposure is crucial, especially during organogenesis. Tailored interventions are essential to optimize outcomes in this unique patient population.